Avaliação da política pública de educação de jovens e adultos: evasão escolar e qualidade de ensino na escola municipal Raul Coelho de Alencar em Barbalha no Ceará - Silva, Eliana Saraiva Batista e (2024)
This research aims to study the trajectory of the educational policy for Youth and Adult Education (EJA) in relation to school dropout rates and the quality of education at Raul Coelho de Alencar Elementary School, located in Barbalha, Ceará. In this regard, it adopts the following specific objectives: to analyze the content of educational policies for youth and adults; to investigate the relationship between school dropout rates and the quality of education within the EJA framework; and to identify pathways within public policies for EJA that may help mitigate school dropout rates. In addition, it seeks, through the evaluation of this public policy, to understand the impediments that prevent these people from going to school, nor from obtaining an education that guarantees them the exercise of a profession and the right to a dignified life. To this end, the chosen methodology is an alternative to approaches that privilege positivist methods, giving way to the experiences of students, through participatory research, within the evaluative perspective proposed by Raul Lejano, in which the experiential approach is based on the post-constructivist interpretative paradigm. Data collection was carried out through the development and application of questionnaires with semi-structured interviews, which supported the focus groups and also through the collection of students' life stories. The evaluation of qualitative data was based on the descriptive analysis of the research, seeking a dense description of the reality of EJA students. EJA subjects are in themselves the living content of teaching. To do so, it is necessary to know them, listen to them and thus trace the path of meaningful learning with them. The theoretical framework used is the Paulo Freire method (2021) as a way of repudiating traditional, “banking” teaching, and defends the construction of learning with meaning, which liberates and promotes awareness. Donna Haraway (2009) is also included, through her article "Situated Knowledges", highlighting the feminist issue as also being an issue specific to EJA. In addition to her, we follow Tim Ingold (2014), who presents us with the importance of experience as a search for the production of knowledge among each other. It also aligns with the thinking of Marcondes and Brisola (2011) when seeking the uniqueness of the subjects that make up EJA, through listening and interest in their trajectories.